1986
DOI: 10.1063/1.96830
|View full text |Cite
|
Sign up to set email alerts
|

Ordered structures in GaAs0.5Sb0.5 alloys grown by organometallic vapor phase epitaxy

Abstract: Electron diffraction measurements on (100) GaAs1−xSbx layers with x≊0.5 grown by organometallic vapor phase epitaxy indicate that ordered phases are formed during growth. Two ordered phases are observed. The simple, tetragonal AuCu-I type phase consists of alternating {100} oriented GaAs and GaSb layers. Only the two variants with the tetragonal c axes perpendicular to the growth direction are observed. At least two variants are observed for the chalcopyrite E11 structure with alternating {210} oriented GaAs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(38 citation statements)
references
References 14 publications
1
36
1
Order By: Relevance
“…In particular, we account for the growth of only two orientations of (111) MSL's (reported for all systems investigated so far), and of only one (110) BSL variant (reported for GaΡ/InΡ [11]). Further, ΔΕsu r for (100) and (111) MSL's are close to each other, which may explain the growth of both phases reported for GaΑs0.5Sb0.5 [12,13]. On the other hand, high ordering of Ga0.51n0.5Ρ in the phase of (111) MSL occurring for high growth temperatures is not explained by the present approach, and is possibly due [8] to the presence of monolayer steps at the surface.…”
mentioning
confidence: 47%
“…In particular, we account for the growth of only two orientations of (111) MSL's (reported for all systems investigated so far), and of only one (110) BSL variant (reported for GaΡ/InΡ [11]). Further, ΔΕsu r for (100) and (111) MSL's are close to each other, which may explain the growth of both phases reported for GaΑs0.5Sb0.5 [12,13]. On the other hand, high ordering of Ga0.51n0.5Ρ in the phase of (111) MSL occurring for high growth temperatures is not explained by the present approach, and is possibly due [8] to the presence of monolayer steps at the surface.…”
mentioning
confidence: 47%
“…It is worth noting that other authors have seen fairly large discrepancies of up to 0.2 eV in the PL energies compared with predictions obtained using tabulated values of the bowing parameters [15]. We have also performed TEM measurements on these samples, which showed ordering in these quaternary material similar to the Cu-Au type observed in GaAsSb [16,17]. Recent PL measurements on GaAsSb ternary alloys indicated that the presence or absence of strong Cu-Au ordering had no effect on the PL energies [17].…”
Section: Resultsmentioning
confidence: 78%
“…Strong bowing indicates a large change in lattice energy, which acts as a driving force for ordering, that is, for compound formation when a stoichiometric atomic ratio is reached rather than the formation of a statistical alloy. Examples are SiGe, GaInP 2 , or Ga 2 AsP (Jen et al 1986;Srivastava et al 1986;Ourmazd and Bean 1985). For In x Ga 1-x N and In x Al 1-x N alloys, see Ferhat and Bechstedt (2002).…”
Section: Bandgap Of Alloysmentioning
confidence: 99%